New clues from Earth's most elusive impact crater: Evidence of reidite in Australasian tektites from Thailand - Cavosie, Aaron; Timms, Nicholas Eric; Erickson, Timmons; Koeberl, C. (Geological Society of America, 2018)
Australasian tektites are enigmatic drops of siliceous impact melt found in an ~8000 Ã— ~13,000 km strewn field over Southeast Asia and Australia, including sites in both the Indian and Pacific oceans. These tektites formed only 790,000 yr ago from an impact crater estimated to be 40-100 km in diameter; yet remarkably, the young and presumably large structure remains undiscovered. Here we report new evidence of a rare high-pressure phase in Australasian tektites that further constrains the location of the source crater. The former presence of reidite, a high-pressure polymorph of zircon, was detected in granular zircon grains within Muong Nong-type tektites from Thailand. The zircon grains are surrounded by tektite glass and are composed of micrometer-sized neoblasts that contain inclusions of ZrO 2 . Each grain consists of neoblasts in three distinct crystallographic orientations as measured by electron backscatter diffraction, where all [001] directions are orthogonal and aligned with one < 110 > direction from the other two orientations. The systematic orientation relationships among zircon neoblasts are a hallmark of the high-pressure polymorphic transformation to reidite and subsequent reversion to zircon. The preserved microstructures and dissociation of zircon to ZrO 2 and SiO 2 require a pressure > 30 GPa and a temperature > 1673 Â°C, which represent the most extreme conditions thus far reported for Australasian Muong Nong-type tektites. The data presented here place further constraints on the distribution of high-pressure phases in Australasian tektites, including coesite and now reidite, to an area centered over Southeast Asia, which appears to be the most likely location of the source crater.